Four-dimensional flow-sensitive MRI of the thoracic aorta: 12- versus 32-channel coil arrays - Stalder, Aurélien F.; Dong, Zhiyuan; Yang, Qi; Bock, Jelena; Hennig, Jürgen; Markl, Michael; Li, Kuncheng (Journal of magnetic resonance imaging, 2012)
Purpose: To evaluate the performance of four‐dimensional (4D) flow‐sensitive MRI in the thoracic aorta using 12‐ and 32‐channel coils and parallel imaging. Materials and Methods: 4D flow‐sensitive MRI was performed in the thoracic aorta of 11 healthy volunteers at 3 Tesla (T) using different coils and parallel imaging (GRAPPA) accelerations (R): (i) 12‐channel coil, R = 2; (ii) 12‐channel coil, R = 3; (iii) 32‐channel coil, R = 3. The quantitative analysis included SNR, residual velocity divergence and length and curvature of traces (streamlines and pathlines) as used for 3D flow visualization. In addition, semi‐quantitative image grading was performed to assess quality of phase‐contrast angiography and 3D flow visualization. Results: Parallel imaging with an acceleration factor R = 3 allowed to save 19.5 ± 5% measurement time compared with R = 2 (14.2 ± 2.4 min). Acquisition using 12 channels with R = 2 and 32 channels with R = 3 produced data with significantly (P < 0.05) higher quality compared with 12 channels and R = 3. There was no significant difference between 12 channels with R = 2 and 32 channels with R = 3 but for the depiction of supra‐aortic branches where the 32‐channel coil proved superior. Conclusion: Using 32‐channel coils is beneficial for 4D flow‐sensitive MRI of the thoracic aorta and can allow for a reduction of total scan time while maintaining overall image quality. J. Magn. Reson. Imaging 2012;35:190‐195. © 2011 Wiley Periodicals, Inc.